PERAN LINGKUNGAN TERHADAP PEMENUHAN HAK ANAK DALAM “L’AUBERGE DE L’ANGE GARDIEN” KARYA COMTESSE DE SEGUR - Juliandari, Lely; Kuswarini, Prasuri; Hasyim, Muhammad (Universitas Hasanuddin, 2017)
The children rights were first recognized in the 19th century, at the time when war wasraging in Europe and many children became victims of war. Comtesse de Segur's novell'Ange Gardien depicts the condition of many children in that century. Implicitly the novelinvites the reader to realize that children must get their rights to grow into a good humanbeing.This study examines the topic of how the environment contributes to the fulfillment of therights of children in the novel l'Ange Gardien by Comtesse de Segur.The method used in this research is descriptive method of analysis with intrinsic approach ofcharacterization and background theory. The characterization theory is used to get thecharacter description and the relation between the characters, while the background theory isused to get the picture of the life background (environment) related to children's rights.Extrinsically the approach of sociology of literature also complement the analysis that linksthe social structure of literary works with the actual social structure of society. So throughliterary works can be understood symptoms and social influences that occur.The results of this study concluded that the character of a well-formed children comes from agood environment as well, and vice versa.Key words: children's rights, the 19th century, sociology of literature, social environment,character.